Kinerja Bank Konvensional Pasca Spin Off Unit Usaha Syariah - Atman Poerwokoesoemo (STIE Indonesia Banking School, 2016)
In the last decade there are four conventional commercial banks succeeds spin off their Islamic Business Unit to become independent commercial Islamic banks. This research objective was to answer the question: do these conventional banks have a different financial performance (CAR, NPL, BOPO, ROA and LDR) between before and after they spin off its Islamic Business Units. This research using Difference Test succeeds to proof that there is difference between before and after they spin off its Islamic Business Unit among these four conventional banks. This research elaborates the financial performance difference using quarterly period of two years’ financial reports before and after spin off each. Hypothesis testing proofed that these five financial ratios shows difference performance between before and after.